1999
DOI: 10.1097/00000542-199909000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphine and Tramadol on Somatic and Visceral Sensory Function and Gastrointestinal Motility after Abdominal Surgery 

Abstract: Pain control was equally effective with morphine and tramadol infusions. No somatic or visceral sensitization was evident during morphine and tramadol infusions, but pain tolerance thresholds as markers of antinociception were increased more during morphine infusions. The significant sensitization seen only after morphine discontinuation may be due to convergent visceral input. Gut motility was prolonged significantly by visceral surgery itself and also by morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 34 publications
0
33
0
2
Order By: Relevance
“…Recently, several groups reported that tramadol has less effects on gastric emptying than morphine. 12,13 The significance of this finding with regard to clinical outcomes remains to be determined. R Re ef fe er re en nc ce es s …”
Section: Objectif : Le Tramadol [(1rs 2rs)-2-diméthylamino) Méthyl-mentioning
confidence: 99%
“…Recently, several groups reported that tramadol has less effects on gastric emptying than morphine. 12,13 The significance of this finding with regard to clinical outcomes remains to be determined. R Re ef fe er re en nc ce es s …”
Section: Objectif : Le Tramadol [(1rs 2rs)-2-diméthylamino) Méthyl-mentioning
confidence: 99%
“…Several studies have demonstrated that tramadol was equally effective in controlling postoperative pain as morphine. 1,2 The synergy of monoaminergic and opioid activity achieves analgesic effects. 3 Administering analgesics before the patient emerges from general anesthesia may result in an "acceptable" comfort level for the patient in the early postoperative period.…”
Section: Brief Reportsmentioning
confidence: 99%
“…However the observed effects may be of greater clinical significance for people where analgesic consumption is higher, such as in patients with mood disorders, younger people and those undergoing procedures associated with higher postoperative analgesic consumption including emergency, major and abdominal surgery [28,29]. Furthermore, the efficacy of tramadol is most of the time not sufficient for more than mild or moderate pain [30], and although it provides other benefits such as reduced respiratory depression [31,32], better management of neuropathic pain [33] and less impairment of gastrointestinal motor function [34,35], there are also a number of theoretical and practical limitations to its use in addition to the clinical significance of the observed interaction with ondansetron. These include involvement in other clinically relevant drug interactions [36], implication in the development of serotonin syndrome [37,38], a possible decrease in seizure threshold, particularly in those at higher risk of seizures [2], and an increased incidence of nausea and vomiting [2].…”
Section: Discussionmentioning
confidence: 99%